Letter to the editor - round table unites to tackle culture change in an effort to improve animal research reporting - Osborne, N; Ritskes-Hoitinga, M; Ahluwahlia, A; Alam, S; Brown, M; Henderson, H; de Leeuw, W; Marsh, J; Moher, D; van Oort, E; Rawle, F; Riederer, B; et al. (BioMed Central, 2017)
A round table discussion was held during the LAVA-ESLAV-ECLAM conference on Reproducibility of Animal Studies on the 25th of September 2017 in Edinburgh. The aim of the round table was to discuss how to enhance the rate at which the quality of reporting animal research can be improved. This signed statement acknowledges the efforts that participant organizations have made towards improving the reporting of animal studies and confirms an ongoing commitment to drive further improvements, calling upon both academics and laboratory animal veterinarians to help make this cultural change.